Heuristic techniques for the design of ultra wideband antenna - Zhang, Zhan. (2009)
The imminent wide scale commercial deployment of ultra-wideband (UWB) systems has led to increased interest in UWB antenna designs. This thesis is motivated by the need for an effective method to design a high performance UWB antenna.